Voltage Response of Three-dimensional RC-medium to Prolonged Step Voltage Change - Veteikis, R. (Elektronika ir Elektrotechnika, 2007)
The analytical expressions of electrotonic potential distribution in three-dimensional ohmic-capacitive medium, when long square voltage pulses are applied, were derived. The expression of half-time (T1/2) derivative in respect to distance (∂T1/2/∂R) was obtained. The dependencies of T1/2 and ∂T1/2/∂R on the voltage electrode dimensions and the distance between the voltage electrode and the potential measurement place were calculated. The calculations demonstrate that the slope of the function T1/2=f(R) depends both on the distance between the potential measurement site and the voltage electrode, as well as the voltage electrode dimensions. Close to the voltage source, the dependence of T1/2 on distance deviates from linear. Ill. 3, bibl. 9 (in English; summaries in English, Russian and Lithuanian).